(untitled) (Physical Education, Health and Social Sciences, 2025)
This study explores the motif of insomnia in Pashto tappa as a culturally embedded literary symptom that reflects emotional, social, and existential tensions in Pashtun life. Drawing on a qualitative content analysis of a purposive corpus of tappa collected from oral traditions, contemporary recordings, and written anthologies, the research employs thematic and semiotic approaches to decode how insomnia is represented, metaphorized, and experienced in these couplets. The analysis reveals that insomnia functions on multiple symbolic registers: as an expression of unfulfilled love and longing, as a manifestation of spiritual or metaphysical restlessness, and as an index of collective anxiety about social dislocation, loss, and identity. In many tappa(s), the inability to sleep is not merely a physiological complaint but a culturally sanctioned language for voicing personal suffering and communal memory. The study situates these representations within broader Pashtun cultural narratives, showing how literary form and affective content coalesce to make insomnia both a personal symptom and a shared cultural discourse. The findings contribute to literary anthropology and affect studies by demonstrating that what appears as a private disturbance in tappa is simultaneously a public cultural signifier, thereby offering a nuanced understanding of emotion, embodiment, and meaning making in Pashto folk literature.